2022
DOI: 10.1515/epoly-2022-0030
|View full text |Cite
|
Sign up to set email alerts
|

Effects of grafting and long-chain branching structures on rheological behavior, crystallization properties, foaming performance, and mechanical properties of polyamide 6

Abstract: Polyamide 6 (PA6) was modified with ethylene maleic anhydride syndiotactic copolymer resin (ZeMac), and triglycidyl isocyanurate (TGIC) as modifiers to prepare a grafting structure and a long-chain branching structure, respectively. The effects of two modifiers on the rheological behavior, crystallization properties, foaming performance, and mechanical properties of PA6 were systematically studied by rotating rheometry, differential scanning calorimetry and scanning electron microscopy. The results showed that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 39 publications
0
5
0
Order By: Relevance
“…In conclusion, several methods have been developed to recycle PA under different compositions and structures: blends, multilayers and (nano)composites. Unfortunately, not much information has been found on PA foams 128 and biobased-PA, 129 as well as the effect of different additives such as flame retardants, antioxidants, stabilizers and plasticizers. 130 Another subject of high interest would be to investigate into more details crosslinked PA. 131 In addition, most of the literature focused on aliphatic polyamides (PA6 and PA6.6).…”
Section: Discussionmentioning
confidence: 99%
“…In conclusion, several methods have been developed to recycle PA under different compositions and structures: blends, multilayers and (nano)composites. Unfortunately, not much information has been found on PA foams 128 and biobased-PA, 129 as well as the effect of different additives such as flame retardants, antioxidants, stabilizers and plasticizers. 130 Another subject of high interest would be to investigate into more details crosslinked PA. 131 In addition, most of the literature focused on aliphatic polyamides (PA6 and PA6.6).…”
Section: Discussionmentioning
confidence: 99%
“…Cao et al selected ethylene-maleic anhydride (ZeMac) grafted PA6 and triglycidyl isocyanurate (TGIC) for chain extension modification. 21 The results showed that the grafting and longchain branching structure improved the entanglement between molecular chains, restricted the movement of molecular chains, and the polymer viscosity increased accordingly, and the viscosity increased with the increase of modifiers. Xu used trifunctional epoxy resin as a crosslinking agent to crosslink PA6 during chemical extrusion foaming molding.…”
Section: Introductionmentioning
confidence: 98%
“…11,12 To enhance the quality and performance of PA6 micro-foam products, it is imperative to address the issue of low melt strength. Several potential solutions include incorporating nano-clay, 11,13 fiber blends, [14][15][16] chain expansion, [17][18][19][20][21] and crosslinking. 22 According to research, adding nano-clay to PA6 can increase its activation energy, improving both the crystallization rate and nucleation efficiency.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations